Emissão de CO2 de materiais de construção civil no Brasil: estimativas na etapa projetual de edificações - Kozloski, Cássia Laire (2020)
The building construction sector is among the major contributors to global warming, due to excessive emissions of carbon dioxide (CO2) by anthropogenic activities. As for buildings, actions to mitigate the environmental impacts caused occur worldwide, both for reducing energy use and for greenhouse gas emissions beyond the operation phase, since the contribution of embodied energy and carbon have increased with the evolution of the thermal efficiency of the systems that make up a building. In this sense, through a Systematic Literature Review (SLR), the present work seeks to identify the context of academic-scientific production and the approaches used in Brazil with regard to the assessments of carbon and energy incorporated in buildings. It leads to support the development of a proposal tool that estimates the initial and recurring embodied carbon (EC) of building construction materials, focusing on the use by professionals during the initial stages of design in Santa Maria, RS. The SLR was carried out for the period from 2010 to 2020 in the CAPES Thesis and Dissertations Catalog and in four international scientific journals bases. Through the analysis of 96 selected national publications, it has been identified a majority of complete and modular Life Cycle Assessments (LCA) carried out and for the borders of “cradle at the gate” and “cradle at the grave”, using secondary data and a timid sensitivity and uncertainty analysis. Moreover, the use os simplifications is mandatory to make such analisys and evaluations feasible, in contrast to the lack of regionalized data. Regarding the tool, a compilation of national secondary data and calculation procedures identified during RSL were used to estimate the CI by material for the “cradle to gate” boundary, and primary data were used from a local survey with commercial establishments for the “gate to ground” boundary, supporting the initial proposal for the elaboration of the tool. The buildings 50 years lifespan was considered, determining the recurring emissions for total replacement of material. These were covered according to the mass representativeness and availability of national data. Concerning the tool proposal, developed in the Microsoft Excel spreadsheet editor, the materials considered were steel, sand, industrialized mortar, gravel, concrete block,lime, cement, ceramic tiles, ceramic, concrete and fiber cement tiles, ceramic brick, and a composition for concrete on site. As an application example for tool validation, an estimate in a specific building was carried out considering eight of these materials, and the emission result, 0.208 tCO2 / m² of the building, approximately 88% of the total when compared to other materials for the same boundary, approaches those obtained by other authors. The tool proposal proved to be efficient in application, mainly to start considering sustainable issues at a design stage, while the SLR results contribute to the understanding of national research on embodied carbon and energy, being able to outline new investigations in the area.